Subjunctive mood in Croatian: searching for a paradigm - Zovko Dinković, Irena (Array, 2004)
The subjunctive mood is nowhere explicitly mentioned in grammars of Croatian and there are no separate verb forms for the subjunctive as we find them in languages such as French. However, aside from the indicative and imperative, the conditional is cited as a third mood in Croatian. The conditional mood has a separate paradigm of verb forms (past and present) used not only in conditional clauses (the so-called if-clauses), but also to express a whole range of subjunctive meanings: wishes, demands, proposals, concession, etc. It is interesting that Croatian employs three other forms to convey the subjunctive meaning: the past perfect tense, the perfective present and the perfective future forms. Whereas the perfective future forms may only appear in if-clauses, the former two may appear either in if-clauses, or in clauses which express some other kind of subjunctive meaning. In many instances conditional verb forms may be replaced by perfective present forms, which apparently causes a change in meaning. This paper therefore investigates two issues: the first one is whether the Croatian conditional is truly equivalent to what in other languages is called the subjunctive mood, and second, what differences in meaning underlie the use of conditional verb forms as opposed to perfective present forms in the same context.